2021
DOI: 10.32601/ejal.911454
|View full text |Cite
|
Sign up to set email alerts
|

Status of English speaking skills in Turkish ELT departments: A nationwide survey

Abstract: The situation of spoken English in both formal and informal settings in Turkey seems to be far from satisfactory. Additionally, the legal arrangements devoted to ameliorate this predicament have proven unsuccessful as far as an acceptable level of competence is concerned. The present study aimed to investigate the situation of English speaking skills at the English Language Teaching (ELT) departments in Turkey, in attempts to attain a descriptive outline for the problems, perceptions, needs, and solutions prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Coursebooks were stated to be another barrier to language learning. Previous studies also showed that exercises in the coursebooks emphasize the importance of grammar and vocabulary, are far from fostering the use of English for communicative purposes (Çapan, 2021;Dağtan & Cabaroğlu, 2021). The current study showed that inflexible and impractical curriculum was another challenge for language learning, which may cause time related-challenges (Akdağ Çimen, 2017;Kızıldağ, 2009;Madalińska-Michalak & Bavli, 2018).…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 63%
See 1 more Smart Citation
“…Coursebooks were stated to be another barrier to language learning. Previous studies also showed that exercises in the coursebooks emphasize the importance of grammar and vocabulary, are far from fostering the use of English for communicative purposes (Çapan, 2021;Dağtan & Cabaroğlu, 2021). The current study showed that inflexible and impractical curriculum was another challenge for language learning, which may cause time related-challenges (Akdağ Çimen, 2017;Kızıldağ, 2009;Madalińska-Michalak & Bavli, 2018).…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 63%
“…As for the student related problems, demotivation, unwillingness, fear of making mistakes and anxiety, lack of interaction, lack of self-confidence, discipline issues, socioeconomic status, and inequality of opportunities were among the most frequently stated problems. Learner demotivation, unwillingness, fear of making mistakes, high anxiety, and lack of self-confidence were commonly mentioned problems of language teaching in the literature (Akdağ Çimen, 2017;Çapan, 2021;Dağtan & Cabaroğlu, 2021;Erdoğan & Tunaz, 2012;Genç & Aydın, 2017;Noom-Ura, 2013). The factors causing learner demotivation can vary from teacher attitude to teaching approach, personal difference, teaching material, social environment, and inappropriate feedback (Akdağ Çimen, 2017;Çapan, 2021;Solak & Bayar, 2015).…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…While most of the above-mentioned studies centered on language learners, there were also some researchers who focused on pre- or in-service teachers, and their speaking skills and practices of teaching speaking to their learners. For instance, Dağtan and Cabaroğlu (2021) and Koşar (2020) focused on pre-service EFL teachers’ oral proficiency, both raising concerns in terms of their low-level of proficiency, fluency, and confidence in speaking. In Yağız's (2018) study, although the EFL teachers found pronunciation important, their content knowledge on teaching pronunciation was limited to segmental features, lacking emphasis on the suprasegmental ones.…”
Section: Classroom Processes and Instructional Practicesmentioning
confidence: 99%
“…Additionally, this study centers on the five macro-skills; hence, it differs from Kwee (2021), which focuses only on three macro-skills: reading, writing, and speaking. Other studies focus on one domain of macro-skill only: listening (Intan et al, 2022); on speaking (Dağtan & Cabaroğlu, 2021;Marzuki & Kuliahana, 2021;Zaitun et al, 2021;Saed et al, 2021;Bawanti & Arifani, 2021;and Khan et al, 2021); on reading (Isagjon, 2022;Mawlood & Abbas, 2022), on writing (Zahari, 2022;Nourazar, 2022;Rodgers et al, 2022;Zeleke, 2022;Galang, 2021;& Zhang & Cheng, 2020); and on viewing (Faloye et al, 2021).…”
Section: Introductionmentioning
confidence: 99%